AUDIENCE RECEPTION ANALYSIS TOWARD POLITICAL MESSAGES IN PRESIDENT JOKO WIDODO YOUTUBE CHANNEL - Kristi Dwi Utami; Puji Lestari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2017)
Youtube audience which is considered as active audience are capable to reception and give the direct feedback. The political messages that was delivered through youtube also have very diverse meaning to audienc. There are message that instantly can be understood by the audience , but also there are some audience that the recived the message in different ways. This research aims to understand the audience reception to political messages which is delivered by jokowi in his Youtube channel as well as the factors that affects the audience reception. This research is qualitative research. This research used data collection technique through focuss group discussion (FGD) and interview. The theory used to analyze the audience reception is decoding-encoding Stuart Hall Theory. This research result indicates that this channel is one of the way to get closer to the community and this channel is public information and political message that choosen by Joko Widodo. There are 5 audience in the dominant hegemonic position and 1 audience in the grey oppositional position. Two new positions which are not included in the audience position according to stuart hall was found in this research. First , the grey oppositional position , happen if audience not capable of reception a message and rejected dominant meaning offered by the message maker. Second , the grey dominant position, happen if audience not capable of reception a message , but agrees with dominant meaning offered by the message maker. The factors that affect youtube audience channel president Joko Widodo in doing reception are, ages factors education background factors, frequency of video watching and like and dislike factors.